2006
DOI: 10.1111/j.1365-294x.2006.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of the phylogeography, Pleistocene history and secondary contact hypotheses for the killifish,Fundulus heteroclitus

Abstract: The mummichog, Fundulus heteroclitus, exhibits extensive latitudinal clinal variation in a number of physiological and biochemical traits, coupled with phylogeographical patterns at mitochondrial and nuclear DNA loci that suggest a complicated history of spatially variable selection and secondary intergradation. This species continues to serve as a model for understanding local and regional adaptation to variable environments. Resolving the influences of historical processes on the distribution of genetic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 63 publications
16
112
2
Order By: Relevance
“…Given the large population sizes of F. heteroclitus in these marshes (on the order of 10 5 individuals; Adams et al. 2006), this is consistent with broad‐scale movements of substantial numbers of fish within large marshes. However, little is known about dispersal between marshes, which would require dispersal across potentially unfavorable habitat along the coast.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Given the large population sizes of F. heteroclitus in these marshes (on the order of 10 5 individuals; Adams et al. 2006), this is consistent with broad‐scale movements of substantial numbers of fish within large marshes. However, little is known about dispersal between marshes, which would require dispersal across potentially unfavorable habitat along the coast.…”
Section: Resultssupporting
confidence: 79%
“…; Adams et al. 2006), which coincides with the southern‐most extent of the Pleistocene ice sheet (Mickelson et al. 1983).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Fundulus heteroclitus macrolepidotus occupies the northern part of the species range and is replaced by F. heteroclitus heteroclitus in the south, with the transition between the two subspecies centred in or just north of New Jersey (Morin and Able, 1983). This variation takes the form of a cline in gene frequencies and phenotypic traits along the coast, with different genetic markers having clines of different steepness (Adams et al, 2006;GonzalezVilasenor and Powers, 1990;Powers et al, 1991;Ropson et al, 1990;Strand et al, 2012). Similar genetic and physiological clines are present in the Chesapeake and Delaware Bays, with F. heteroclitus heteroclitus (the southern subspecies) dominating at the coast and F. heteroclitus macrolepidotus dominating the freshwater reaches of these large estuaries (Powers et al, 1991).…”
Section: Killifish Geneticsmentioning
confidence: 99%
“…In addition, also physical parameters, such as temperature, salinity, oxygen concentration, ocean depth and pollution gradients have been described to be important for creating population structure in marine fishes. Wellknown examples include both latitudinal differences in temperature on the east coast of North America and salinity differences in the transition zone from the highsaline North Sea into the brackish Baltic Sea, where several studies have demonstrated high levels of genetic differentiation, isolation by distance and local adaptation among populations (Nielsen et al, 2003(Nielsen et al, , 2004Scott and Schulte, 2005;Adams et al, 2006;Fangue et al, 2006;Larsen et al, 2007;Hemmer-Hansen et al, 2007a). Alternatively, environmental variation can also result in changes in important life history parameters that potentially can result in subdivision in marine fishes.…”
Section: Evolutionary Realistic Scenario?mentioning
confidence: 99%